Spirituality in Healthcare: Perspectives for Innovative Practice - Timmins, Fiona; Caldeira, Sílvia (Springer eBooks Medicine, 2019)
What is Spirituality? -- The psychology of spirituality and religion in healthcare -- Spiritual assessment in healthcare: an overview of comprehensive, sensitive approaches to spiritual assessment for use within the interdisciplinary healthcare team -- Spirituality is a Public Health Issue – The potential role of spirituality in promoting health -- Health Outcomes of Religious and Spiritual Belief, Behavior, and Belonging: Implications for Healthcare Professionals -- Spirituality and Childbirth -- Providing spiritual care – An exploration of required spiritual care competencies in health care and their impact on health care provision -- The role of the nurse in providing spiritual care – A case study approach to exploring specific care provision by healthcare workers in the context of an interdisciplinary healthcare team -- Loss and Grief in people with Intellectual disability -- The Role of the Healthcare Chaplain – A summary of the contribution of healthcare chaplains to modern health care practice -- Teaching and Learning about Spirituality in Healthcare Practice Settings -- Working with diversity – An overview of diversity in contemporary society and the effect of this on healthcare situations -- Being Human: Cultivating Mindfulness and Compassion for Daily Living